2017
DOI: 10.1136/bmjopen-2017-016270
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with fewer than 20 remaining teeth in Taiwanese adults with disabilities: a community-based cross-sectional study

Abstract: ObjectivesTo examine the prevalence of and the factors associated with a number of remaining teeth (NRT) <20 among adults with disabilities.DesignA community-based, cross-sectional descriptive study.SettingThis study was part of a health promotion programme designed for community-dwelling adults with disabilities.ParticipantsA total of 549 adults with disabilities, aged 20–80 years, living in the community in Chiayi County in Taiwan.Outcome measuresVarious parameters, including NRT, oral health behaviours (ie,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
5
13
0
2
Order By: Relevance
“…Our findings are similar to those obtained by Leroy and Declerck, for a population of 656 adults with various disabilities, in which 33% of the participants had 20 or less teeth . Note also that studies comparing individuals with physical disabilities and individuals with intellectual disabilities show that those with intellectual disabilities are more likely to have fewer teeth …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are similar to those obtained by Leroy and Declerck, for a population of 656 adults with various disabilities, in which 33% of the participants had 20 or less teeth . Note also that studies comparing individuals with physical disabilities and individuals with intellectual disabilities show that those with intellectual disabilities are more likely to have fewer teeth …”
Section: Discussionsupporting
confidence: 90%
“…Compared to other populations with disabilities, Liu et al 27 and Pradhan et al 28 found that 76.4% and 73% of the respondents, respectively, had not visited the dentist in the last year, similar to estimates for other disadvantaged groups, such as the homeless, 28 but considerably higher than those of our study, possibly due to differences in sample composition. Pan et al 29 also observed that 78% of the individuals with disability did not undergo regular appointments every 6 months, like our sample, in which 71.6% of the individuals had not visited the dentist in the last 6 months.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to the WHO global disability action plan 2014-2021, there are approximately one billion disabled people globally (WHO, 2015). Existing studies report that people with disabilities have poorer oral health than people without disabilities (Chen et al, 2016;Pan et al, 2017;Rashid-Kandvani, Nicolau, & Bedos, 2015). These disabled people live in complex circumstances depending on the severity of their disabilities, including difficulty functioning, experiencing a combination of diseases (Dougall & Fiske, 2008a) and deficiencies in well-organized dental care services for people with special needs (Rashid-Kandvani et al, 2015;Sermsuti-Anuwat & Pongpanich, 2018a, 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the oral health of persons with physical disabilities, few studies have investigated the difficulties in accessing dental services (Chen et al, 2016;Leal Rocha et al, 2015;Rashid-Kandvani et al, 2015;Sermsuti-Anuwat & Pongpanich, 2018b). However, proper daily oral hygiene practices are necessary for persons with a permanent disability (Dougall & Fiske, 2008b;Kothari et al, 2017;Pan et al, 2017). There is limited evidence regarding the factors associated with periodontal diseases and oral hygiene status among independent, community-dwelling, adults with physical disabilities, who are capable of performing their own daily self-care.…”
Section: Introductionmentioning
confidence: 99%